E-Business: New Business Models And Strategies - Tan, Cathy Kwee Tian (2000)
This paper investigates how companies create new business model and strategies to compete online. It is not meant to be an exhaustive, precise analysis of all the difference of e-business models. It does not discuss about technology underpinnings. However, it sets to examine key elements of successful models and strategies in e-business.